RESPON TANAMAN SAWI (Brassica juncea L.)TERHADAP PEMBERIAN BEBERAPA DOSIS BOKASHI SAMPAH PASAR DENGAN DUA KALI PENANAMAN SECARA VERTIKULTUR - AULIA RANI ANNISAVA; LESTI ANJELA; BAKHENDRI SOLFAN (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
Mustard is one of the horticultural crops that have commercial value and nutritious. The research was done in September to December 2013 in Faculty of Agriculture and Animal Sciences Experimental Garden, State Islamic University of Sultan Syarif Kasim Riau. This research was carried out to study the doses of market waste bokashi, planting period and the interaction both of them to planting mustard plants in verticulture system. Randomized Complete Block Design (RCBD) with five replications was used. Treatments involved two factors, i.e. market waste bokashi doses (0, 150, 300, 450 and 600 g per gutters) and planting period (first and second). Observations were done on six morpho-agronomic characteristics, i.e. plant height, number of leaves, leaf length, leaf width, canopy wet weight and canopy dry weight. The results showed that the giving of bokashi 300 g/gutters in the first planting period gives the best results on plant height (28,88 cm), number of leaves (8,28 strands), leaf length (16,30 cm), leaf width (12,93 cm) and canopy wet weight (37,98 g). Bokashi 600 g per gutters on the second planting period gave similar results by using bokashi 300 g per gutters in the first planting period.